PERAN GURU AKIDAH AKHLAK DALAM MEMBENTUK NILAI-NILAI TOLERANSI SISWA DI MA AN-NUR BULULAWANG - Ahmad Muzahim; Anwar Sa’dullah; Kukuh Santoso (VICRATINA, 2022)
The role of the moral aqidah teacher is an important component in forming the values of tolerance in schools. Teachers of moral creed form the values of tolerance through the teaching and learning process. In this case, what is meant is to instill tolerance values directly through learning whose material is directly related to tolerance values. The purpose of this research is to (1) identify the application of student tolerance values at MA An-Nur Bululawang. (2) describe the role of Akidah Akhlak teachers in shaping student tolerance values at MA An-Nur Bululawang. (3) identify barriers and supports in shaping student tolerance values at MA An-Nur Bululawang.